Development of a user-friendly interface routine in C++ for arithmetic and statistical processing of census data - doi: 10.4025/actascitechnol.v35i1.13618 - Lourenço, Roberto Wagner (2012)
A routine was developed in C++ for the processing of social and environmental census data acquired by the Brazilian Institute of Geography and Statistics (IBGE). The routine employs a simple graphical environment. The data generated are presented in a tabular format, which facilitates a broad and objective view of the values, and provides a convenient means of querying the database. The source code used to develop the routine permits updates and changes, as required by the user. Statistical and mathematical analysis enables the generation of social and environmental indicators, together with quantitative and qualitative classification of the socio-environmental quality of the region analyzed. As an example, the routine was applied using census data for the city of Sorocaba (São Paulo State, Brazil), including conditions of household occupation, water supply, sanitation, level of education, income, and other factors. It is envisaged that the proposed analytical model will assist professionals from different fields of research and teaching to develop urban planning and management strategies.